(untitled) (Research, Society and Development, 2023)
Oral mucositis is a common side effect associated with cancer therapeutic modalities. This work aims to develop a semi-solid formulation using epiisopiloturine (EPI) as active principle, evaluating the stability and its in vitro release profile. EPI was combined with the excipients: carbopol, methylparaben, glycerin, triethanolamine, water, vaseline, lanolin and menthol. For physical-chemical evaluation, centrifugation, pH, ice-thaw cycle and organoleptic characteristics tests were carried out. The pH test data were analyzed by the t test and the release data analyzed by linear regression and mathematical models were applied. The analysis of the other results was through descriptive statistics. The results showed that in the centrifugation test, there was no phase separation. In the pH test, the results demonstrated that there was no statistical difference when comparing the pH values between the time 0 and 30 days, being 6.27 and 6.33, respectively. In the ice-thaw cycle test, after the temperature variation cycles, the sample was centrifuged, and it was possible to observe a slight phase separation. In the organoleptic evaluation, a bright white, homogeneous ointment with a mint odor was observed. It presented a release profile of the active principle for approximately 9 hours. PPE can represent a promising alternative. The results of this study can contribute to the development of stable formulations and a product with the potential to be used in association with anticancer treatment, in the fight against side effects such as oral mucositis.